Gauging the Effect of U.S. Tobacco Control Policies From 1965 Through 2014 Using SimSmoke - Levy, David T. (Am J Prev Med, 2015)
INTRODUCTION: The year 2014 marked the 50th Anniversary of the first Surgeon General’s Report. This paper estimates the effect of tobacco control policies in the U.S. after the 1964 Report using the SimSmoke tobacco control simulation model. METHODS: SimSmoke uses National Health Interview Survey data from 1965 through 2012 on smoking prevalence, initiation, and -cessation rates, and incorporates policies implemented since 1965. The model projects smoking prevalence and smoking-attributable deaths (SADs) from 1965 through 2065 and is validated against National Health Interview Survey data. Counterfactual scenarios with policies constant since 1965 and with individual policies are estimated. Analysis was conducted in February 2014. RESULTS: SimSmoke generally validated well over the time period 1965 through 2012. As a result of all policies, smoking prevalence is estimated to have fallen by almost 55% by 2014 with a total of 2 million SADs s averted from 1965 through 2014, increasing to 20.1 million SADs by 2065. The Fairness Doctrine is estimated to have reduced adult smoking prevalence by about 24% by 2014 and averted 10.4 million SADs by 2065, while price increases reduced smoking prevalence by 24% by 2014 and averted 7.3 million SADs by 2065. Smoke-free air laws, cessation treatment, and tobacco control spending individually reduced smoking rates by 3%–5.5% by 2014. CONCLUSIONS: By 2014, SimSmoke predicts a 53% reduction in smoking rates and almost 2 million SADs averted due to polices implemented since the 1964 Surgeon General’s Report, with most of the health benefit still to occur in future years.